Study on the Preparation of Virgin Coconut Oil Using the Cooling Method - Sophia Grace Sipahelut (BIOSAINSTEK, 2025)
Virgin Coconut Oil (VCO) is becoming increasingly popular as public awareness of the importance of health through the use of natural ingredients increases.  The fatty acids and antioxidants in VCO make a major contribution to body health. The nutritional content of the VCO produced is influenced by the processing method.   The purpose of this study was to determine the duration of standing coconut cream after being frozen which can produce VCO with high yield, lowest water content, and most preferred by consumers. The research method used was an experimental method using the treatment of the duration of standing of coconut cream (12 hours, 18 hours, and 24 hours). The parameters observed included yield, water content and consumer acceptance including aroma, color, taste, viscosity and rancidity of VCO produced using 30 semi-trained panelists. The results showed that the duration of standing coconut cream significantly affected the yield and water content. A standing time of 18 hours can provide the best VCO results based on yield (30.33%), water content (0.18%), and consumer acceptance of aroma, color, taste, viscosity, and rancidity on a scale of liking.